Pengaruh Free Cash Flow terhadap Manajemen Laba: Studi pada Perusahaan Jasa Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019 - Watriani Watriani; Vanica Serly (Universitas Negeri Padang, 2021)
This study aims to determine and analyze the effect of free cash flow on earnings management in property and real estate service sector companies listed on the Indonesia Stock Exchange. Earnings management is measured by discretionary accruals using the Modified Jones Model. The population in this study is 62 property and real estate sectors listed on the Indonesia Stock Exchange for the period 2017 to 2019. Based on purposive sampling, a sample of 20 companies was obtained. The analytical method used is a simple panel data regression analysis method using application eviews 10. The results of this study indicate that free cash flow has a significant positive effect on earnings management.